Effective skin care management in postmenopausal women - Saroso, Ade Firman; Sutanto, Hans Utama; Adriani, Donna; Rachmiyani, Irmiya; Khusfiani, Triasti; Putri, Mustika Anggiane (Journal of Society Medicine, 2023)
Menopause-induced hormonal changes can lead to skin problems. The decline in estradiol levels can adversely affect various physiological functions, including skin changes like atrophy, wrinkles, poor wound healing, and a decline in perceived facial attractiveness due to reduced hydration. Effective skincare that can be done to prevent the above problems is by drinking 8 glasses of water a day, consuming vitamins, one of which is vitamin C, consuming antioxidants, using sunscreen, using facial moisturizer, and cleaning your face properly and appropriately. Vitamin C has antioxidant properties and plays an important role in collagen formation. Vitamin C is often found as a constituent of the dermis and epidermis layers in normal skin. However, due to the aging process, the vitamin C content in the dermis and epidermis layers could decrease. Vitamin C has been shown to stabilize collagen mRNA, thereby increasing collagen synthesis to improve skin aging. By implementing these strategies, postmenopausal women can effectively manage skincare and maintain healthy, beauty, vibrant, and glowing skin that looks and feels great.